Development and external validation of new ultrasound‐based mathematical models for preoperative prediction of high‐risk endometrial cancer. (May 2014) - Van Holsbeke, C.; Ameye, L.; Testa, A. C.; Mascilini, F.; Lindqvist, P.; Fischerova, D.; Frühauf, F.; Fransis, S.; de Jonge, E.; Timmerman, D.; Epstein, E.
ABSTRACT Objectives To develop and validate strategies, using new ultrasound‐based mathematical models, for the prediction of high‐risk endometrial cancer and compare them with strategies using previously developed models or the use of preoperative grading only. Methods Women with endometrial cancer were prospectively examined using two‐dimensional (2D) and three‐dimensional (3D) gray‐scale and color Doppler ultrasound imaging. More than 25 ultrasound, demographic and histological variables were analyzed. Two logistic regression models were developed: one 'objective' model using mainly objective variables; and one 'subjective' model including subjective variables (i.e. subjective impression of myometrial and cervical invasion, preoperative grade and demographic variables). The following strategies were validated: a one‐step strategy using only preoperative grading and two‐step strategies using preoperative grading as the first step and one of the new models, subjective assessment or previously developed models as a second step. Results One‐hundred and twenty‐five patients were included in the development set and 211 were included in the validation set. The 'objective' model retained preoperative grade and minimal tumor‐free myometrium as variables. The 'subjective' model retained preoperative grade and subjective assessment of myometrial invasion. On external validation, the performance of the new models was similar to that on the development set. Sensitivity for the two‐step strategy with the 'objective' model was 78% (95% CI, 69–84%) at a cut‐off of 0.50, 82% (95% CI, 74–88%) for the strategy with the 'subjective' model and 83% (95% CI, 75–88%) for that with subjective assessment. Specificity was 68% (95% CI, 58–77%), 72% (95% CI, 62–80%) and 71% (95% CI, 61–79%) respectively. The two‐step strategies detected up to twice as many high‐risk cases as preoperative grading only. The new models had a significantly higher sensitivity than did previously developed models, at the same specificity. Conclusion Two‐step strategies with 'new' ultrasound‐based models predict high‐risk endometrial cancers with good accuracy and do this better than do previously developed models. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.